Influence of social media on civic attitudes in the democratic context of sma students - Ali, Muh; Bambang Murdiansyah, Eko (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This study is motivated by the rapid development of information technology, which significantly influences the civic character of the younger generation, particularly through social media. Kolaka Regency, with a total of 12,276 senior high school students or their equivalents, serves as a strategic location to examine the impact of social media on civic consciousness in the context of democracy. The research questions focus on the characteristics of students' social media usage, its influence on democratic awareness, the challenges faced, and applicable digital literacy strategies. This research uses a survey method with a quantitative approach. The findings reveal that the majority of students do not yet understand democracy as part of civic education through social media. Internal factors, such as a narrow understanding of citizenship and the limited role of family and social environment, along with external factors like the lack of outreach from local governments and electoral institutions, constitute major challenges. As a solution, structured and collaborative digital literacy strategies are needed, involving the government, academics, and electoral institutions to provide relevant educational content and foster critical and participatory civic awareness. Thus, social media can be optimized as a tool to strengthen democratic values among the younger generation toward the vision of Golden Indonesia 2045